Concept of Punishment and Its Justification in Indian Perspective: An Overview - Vijay Lakshmi Mishra, Dr. Krishna Mohan Malviya (European Economic Letters (EEL), 2025)
Punishment is a foundational element of criminal justice, serving as society’s response to crime. This paper provides a comprehensive overview of the concept of punishment and its various justifications, examined through a blend of legal, philosophical, sociological, and criminological perspectives with a focus on India. We outline the major theories of punishment – retributive, deterrent, preventive, reformative, and restorative – and discuss their philosophical underpinnings and goals. The evolution of penal thought in India is traced from ancient times (as reflected in texts like the Manusmriti and Arthashastra, which emphasized order and retribution) through the colonial era (which introduced a uniform penal code focused on deterrence and authority) to the modern Indian legal system (which strives to balance multiple objectives of punishment). We analyze how Indian law and courts have justified and applied punishment, highlighting key developments such as the enshrinement of “rarest of rare” doctrine for capital punishment and an increasing emphasis on reform and rehabilitation in recent decades. Sociological issues, including the high proportion of undertrial prisoners and challenges like prison overcrowding and recidivism, are discussed to assess the effectiveness and humaneness of the current system. The paper concludes that while India’s penal philosophy officially endorses a reformative outlook in many contexts, in practice a combination of justifications – retributive for heinous offenses, deterrent for potential offenders, preventive for habitual criminals, and limited restorative measures – co-exist. It calls for a more structured sentencing framework and greater incorporation of rehabilitative and restorative justice principles to ensure punishment in India meets its aims of justice, public safety, and social betterment.